Albania’s Political Integrity: From Decommunization To Decriminalization (1990-2015) - Krasniqi, Afrim; Bërdufi, Dorina (Acta Universitatis Danubius. Juridica, 2025)
This study examines the evolution of vetting reforms in Albania between 1990 and 2015, focusing on efforts to strengthen political integrity through decommunization and decriminalization measures. It draws upon literature on transitional justice and political reform in post-communist Europe. The research employs qualitative analysis of legislative texts, political narratives, and institutional reform efforts. Findings indicate that early decommunization aimed at purging political influence from the communist era, while subsequent decriminalization addressed broader ethical concerns and criminal infiltration in politics. The study provides insights for policymakers and scholars interested in democratic consolidation and anti-corruption strategies. By linking distinct reform phases across historical contexts, this paper offers a unique case study of Albania’s evolving political integrity framework.